Physical activity and sedentary behaviour of primary school learners in the Eastern Cape province of South Africa - Howard Gomwe; Eunice Seekoe; Philemon Lyoka; Chioneso S. Marange; Dennyford Mafa (South African Family Practice)
Background: This study was designed to assess physical activity (PA) levels and sedentary behaviour amongst primary school learners in the Eastern Cape province of South Africa.